LECTURERS’ PERCEPTION OF THE EFFECTS OF PEER REVIEW AND STUDENTS’ EVALUATION OF TEACHING ON QUALITY TEACHING - Izuagba, Angela C.; Patricia, Nkwocha C. (Sokoto Educational Review, 2020)
The researchers set out to find out if the incorporation of peer review of teaching and students’ evaluation of teaching in the assessment for promotion of lecturers in tertiary institution can enhance the quality of teaching and learning. The research was guided by two mdl hypotheses and a 14 item structured questionnaire was administered on 300 respondents drawn from two tertiary institutions in the south east Nigeria and chi-square was used for data analysis. The finding revealed that the use of peer review and students evaluation of teaching will enhance quality of teaching in our tertiary institutions.